Narratives of statelessness and political belonging among Kurdish diasporas in Sweden and the UK - Eliassi, B (International Migration Institute, 2015)
This paper investigates the phenomenon of statelessness and political belonging in a world of unequal nation-states and citizenship regimes. In so doing it will examine the theoretical construction and conceptions of the stateless in contemporary social and political thought and assess their implications for the conceptions of shared identity and citizenship rights in the legal-political framework of the nation-state and international legal processes and practices. In the academic field statelessness has been largely viewed in relation to the 'lack’ of citizenship and the acquisition of citizenship has therefore been presented as a solution to statelessness. Although citizenship rights and membership of an internationally recognized state are central to the human rights of political subjects in the contemporary world, the conditions and experiences of statelessness do not fade away through acquisition of formal citizenship as the persistent political, legal and military struggles of the stateless groups around the world show. It is therefore important to investigate how notions of political belonging underpinning political projects and collective action of the stateless peoples are constructed and how they inform and shape the evolution of national consciousness among them. Political belonging creates collective goals to sustain or transform political order. This study combines theoretical investigation of statelessness and citizenship with empirical field research on the subjective experiences of the phenomena among the Kurds. Through deploying a narrative inquiry and in-depth interviews, this project will use the narratives of Kurdish migrants in Sweden and the UK to analyze how national consciousness emerges in the absence of a nation-state but also the role of the nation-state in shaping discourses about statelessness and political belonging outside of the 'original’ homelands.